Illusion of Expertise in Portfolio Decisions - An Experimental Approach - Gerlinde Fellner; Werner Güth; Boris Maciejovsky (Center for Economic Studies and ifo Institute (CESifo), 2001)
Overall, 72 subjects invest their endowment in four risky assets. Each com-bination of assets yields the same expected return and variance of returns. Illusion of expertise prevails when one prefers nevertheless the self-selected portfolio. After being randomly assigned to groups of four subjects are asked to elect their expert based on responses to a prior decision task. Using the random price mecha-nism reveals that 64% of the subjects prefer their own portfolio over the average group portfolio or the expert's port-folio. Illusion of expertise is shown to be stable individually, over alternatives, and for both eliciting methods, willingness to pay and to accept.
Keywords: 330; investment decisions; portfolio selection; overconfidence; unrealistic optimism; illusion of control; endowment effect